2015
DOI: 10.1186/s12967-015-0559-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel xeno-free human heart matrix-derived three-dimensional scaffolds

Abstract: RationaleMyocardial infarction (MI) results in damaged heart tissue which can progress to severely reduce cardiac function, leading to death. Recent studies have injected dissociated, suspended cardiac cells into coronary arteries to restore function with limited results attributed to poor cell retention and cell death. Extracellular matrix (ECM) injected into damaged cardiac tissue sites show some promising effects. However, combined use of human cardiac ECM and cardiac cells may produce superior benefits to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Human heart derived decellularized ECM has enabled the seeding and survival of human cardiomyocytes and maintained representative phenotypes of the seeded cardiomyocytes including expression of cardiomyocyte-specific markers and remained electrically synchronous within the scaffold in vitro. 15 Cardiac patches made of rat decellularized cardiac tissue and induced pluripotent stem cells (iPSCs) derived cardiac cells have been proven to improve heart function in vivo. 16 However, perfusion limitations still exist for cardiac scaffolds derived from decellularized matrix affecting the efficacy and efficiency of their applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human heart derived decellularized ECM has enabled the seeding and survival of human cardiomyocytes and maintained representative phenotypes of the seeded cardiomyocytes including expression of cardiomyocyte-specific markers and remained electrically synchronous within the scaffold in vitro. 15 Cardiac patches made of rat decellularized cardiac tissue and induced pluripotent stem cells (iPSCs) derived cardiac cells have been proven to improve heart function in vivo. 16 However, perfusion limitations still exist for cardiac scaffolds derived from decellularized matrix affecting the efficacy and efficiency of their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other natural or synthetic scaffolds, decellularized ECM offers many unique advantages such as preserving organ specific microstructure, mechanical properties, and biochemical cues in favor of cell attachment, growth, and tissue specific differentiation. Decellularized cardiac ECM has also been explored to be used to facilitate cardiac repair. Human heart derived decellularized ECM has enabled the seeding and survival of human cardiomyocytes and maintained representative phenotypes of the seeded cardiomyocytes including expression of cardiomyocyte-specific markers and remained electrically synchronous within the scaffold in vitro . Cardiac patches made of rat decellularized cardiac tissue and induced pluripotent stem cells (iPSCs) derived cardiac cells have been proven to improve heart function in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…However, we have performed labeling trials on these cells and genes in a patch for our othe studies. We evaluated only one route of delivery, direct myocardial injection, and not others such as intravenous, endocardial, intracoronary, and/or a patch 70,71 . Some of these would not be feasible in the current mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have also shown that hiPSC-cardiomyocytes can easily attach to a variety of extracellular materials, including Matrigel, fibronectin, laminin, vitronectin, and other extracellular components (Lundy et al, 2013; Burridge et al, 2014; Holt-Casper et al, 2015; Badenes et al, 2016; Ronaldson-Bouchard et al, 2018). This versatility in attaching to different extracellular components also enables the potential of culturing cells in a microenvironment that may recreate a cardiac extracellular matrix (Rienks et al, 2014; Wang et al, 2016; Li et al, 2018).…”
Section: From Cells To Microengineered Devicesmentioning
confidence: 99%